The impact of chronic kidney disease on long-term outcomes following semi-urgent and elective percutaneous coronary intervention. Issue 6 (September 2021) - Soh, Rodney Yu-Hang; Sia, Ching-Hui; Lau, Rui-Huai; Ho, Pei-Ying; Timothy, Ng Yi-Ming; Ho, Jamie Sin-Ying; Kaur, Harsharon; Sim, Hui-Wen; Yeo, Tiong-Cheng; Tan, Huay-Cheem; Chan, Mark Yan-Yee; Loh, Joshua Ping-Yun
Abstract : Introduction: The effects of chronic kidney disease (CKD) on outcomes in patients undergoing semi-urgent and elective percutaneous coronary intervention (PCI) are unclear. This study aims to investigate impact of CKD on long-term outcomes of this population. Methods: This was a retrospective cohort study of patients who underwent semi-urgent and elective PCI from 1 January 2014 to 31 December 2015 at a tertiary academic center. They were stratified into five groups – group 1 [estimated glomerular filtration rate (eGFR) ≥90 ml/min/1.73m2], group 2 (eGFR 60–89 ml/min/1.73m2), group 3 (eGFR 30–59 ml/min/1.73 m2), group 4 (eGFR <30 ml/min/1.73m2), and group 5 (dialysis). Demographics, risk factors in relation to endpoints of all-cause mortality, contrast-induced nephropathy (CIN), three-point major adverse cardiac events (MACE) (cardiac death, subsequent myocardial infarction, subsequent stroke), and four-point MACE (including target lesion revascularization) were analyzed. Results: One thousand six hundred nine patients were included. Advanced CKD patients were more likely to be female and older, with higher prevalence of co-morbidities. Compared to group 1, group 4 patients were associated with increased risk of three-point [adjusted hazard ratio (aHR) 1.94, 95% confidence interval (CI): 1.06–3.55; P = 0.031] and four-point MACE (aHR 2.15, 95% CI: 1.21–3.80; P = 0.009). However, higher contrast volume usage [odds ratio (OR) 2.20, 95% CI: 1.04–4.68; P = 0.040) was associated with increased CIN risk but not reduced eGFR (OR 1.62, 95% CI: 0.57–4.65; P = 0.369). Conclusion: Advanced CKD patients undergoing PCI were associated with higher co-morbid burden. Despite adjustments for co-morbidities, these patients had higher mortality and worse cardiovascular outcomes at 3 years following contemporary PCI.